2014
DOI: 10.2138/am.2014.4628
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the formation of chalcopyrite and bornite via the sulfidation of hematite: Mineral replacements with a large volume increase

Abstract: Chalcopyrite (CuFeS 2 ) and bornite (Cu 5 FeS 4 ) are the most abundant Cu-bearing minerals in hydrothermal Cu deposits, forming under a wide range of conditions from moderate-temperature sedimentary exhalative deposits to high-temperature porphyry Cu and skarn deposits. We report the hydrothermal synthesis of both chalcopyrite and bornite at 200-300 °C under hydrothermal conditions. Both minerals formed via the sulfidation of hematite in solutions containing Cu(I) (as a chloride complex) and hydrosulfide, at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 48 publications
(46 reference statements)
1
15
0
Order By: Relevance
“…In U-free experiments, chalcopyrite replaced hematite directly (Zhao et al 2014a). In contrast, the presence of U…”
Section: Accepted Manuscriptmentioning
confidence: 95%
See 2 more Smart Citations
“…In U-free experiments, chalcopyrite replaced hematite directly (Zhao et al 2014a). In contrast, the presence of U…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…7c). Li et al (2015) and Zhao et al (2014a) observed that the replacement of hematite (Fe 2 O 3 ) by chalcopyrite (CuFeS 2 ; V m ~ +196%; Table 1) results in both a porous chalcopyrite that replaces the hematite in a pseudomorphic manner, and a chalcopyrite overgrowth that grows from solution. Hence, it is clear that such a large volume increase is accommodated through the transport of species away from the replacement interface rather than via reaction-induced fracturing as has been observed in other systems exhibiting a volume increase (Jamtveit et al 2009;Plümper et al 2012;Putnis et al 2007b).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that the Cu-Fe sulfide minerals at Olympic Dam originally formed by the replacement of hematite, and have subsequently been remobilized (Haynes et al 1995). Recently Zhao et al (2014a) was able to form chalcopyrite and bornite by the replacement of hematite under hydrothermal conditions. Again it is a surprising feature that these nominally massive sulfide ore minerals have such a relatively high porosity.…”
Section: Chalcopyrite and Bornitementioning
confidence: 99%
“…In all cases the product mineral showed evidence of reaction generated porosity. The ore-forming reactions that have been studied include the replacement of pentlandite by violarite (Tenailleau et al 2006;Xia et al 2009Xia et al , 2008Xia et al , 2007, pyrrhotite by marcasite and pyrite (Qian et al 2011;Xia et al 2010Xia et al , 2007, hematite by chalcopyrite (Zhao et al 2014b), chalcopyrite by bornite (Zhao et al 2014a), magnetite by pyrite (Qian et al 2010) and by arsenian-pyrite (Qian et al 2013), calaverite by gold (Zhao et al 2009, and sylvanite and krennerite by gold-silver alloy (Xu et al 2013;Zhao et al 2013). In all these replacement reactions, porosity was generated in the daughter minerals regardless whether the reaction involves volume contraction or expansion.…”
Section: Introductionmentioning
confidence: 99%